Referrals from Paediatric Department with Respiratory Symptoms having Skin Lesions - Jha, Sagar Mani; Budhathoki, Lee; Shakya, Nabin Bhakta; Shakya, Sunil; Roka, Kumar (Journal of Nepal Paediatric Society, 2021)
Introduction: Paediatric patients with respiratory symptoms having skin lesions are often referred from Paediatric to Dermatology Department. Knowledge about skin and respiratory manifestations will lead to early diagnosis and proper management by the doctors of both the specialties. These dermatological conditions may or may not be related to respiratory illness or may hence be part of total disease process or may be completely separate entity. The aim of this study was to find out skin manifestations of various respiratory diseases and analyse dermatological disorders in children referred from Paediatric Department having respiratory symptoms. Methods: An observational cross sectional hospital based study involving inpatients and outpatients referred from Paediatrics to Dermatology Department having respiratory illness and skin lesions was undertaken between January 2019 to December 2020. Details of skin disease were recorded. The descriptive statistical analysis was expressed in frequency and percentage and Chi square test was applied to determine significance among variables. Results: Total 437 patients were included in the study. The most common diagnosis made by Paediatric 160 (36.6%) and Dermatology Departments 246 (56.2%) was viral exanthema followed by atopic dermatitis 77 (17.6%). Out of total 65 patients who suffered from bronchial asthma, 59 (90.7%) patients had atopic dermatitis. Conclusions: Significant paediatric patients with respiratory illnesses have concomitant skin lesions. There is very high percentage of patients having atopic dermatitis among those who had asthma and hence clearly depicts relation between the two diseases.